(untitled) (Texas Journal of Philology, Culture and History, 2025)
The article explores the issues of preserving traditional residential houses in the city of Shahrisabz and examines key principles for the integration of residential neighborhoods into a unified urban structure. Comparative examples are drawn from the historic cities of Khiva, Bukhara, and Samarkand.